The relationship between activity of daily living (ADL) and quality of life among the elderly people - Trinidad, Felix Tito; Sutiyarsih, Emy; Pradikatama, Yafet (JOURNAL OF Mental Health Concerns, 2026)
Background: Continued​ age (≥60 years) experienced decline function physical and psychological that can influence Activities of Daily Living (ADL) such as bathing, dressing, eating, and transferring. Level of independence plays a role in ADL important to quality life elderly, because influence freedom activities, interactions social, as well as welfare physical and mental. Purpose: To know the relationship between the level of independence activities of daily living (ADL) with quality life expectancy in the elderly. Method: Non-experimental design with approach cross-sectional. Population study is all over elderly at LKS-LU Pangesti Lawang. Samples taken with technique purposive sampling. Instrument study covering ADL questionnaire with Barthel Index (BI) for measure level independence and WHOQOL-BREF For measure quality live. Data analysis was carried out using the Spearman Rank test. Results: Spearman's correlation test results show that there is very strong and significant relationship between ability activity daily activities (ADL) with quality life, things This indicated by the value coefficient correlation Spearman's value is 0.916 and significance of 0.000 (p < 0.01). Findings This indicates that the taller ability activity daily someone, then the better quality his life. Conclusion: There is connection meaningful between ADL level with quality life elderly. Improvement independence in ADL necessary become focus intervention for maintain and improve quality life elderly. Keywords: Activity Of Daily Living; Continue Age; Independence; Quality Life.